A TRADUÇÃO NO CONTEXTO DO MUNDO GLOBALIZADO - Darin, Leila Cristina de Mello (2010)
Ever since the invention of writing, translation has played a major role the interaction between peoples and cultures. Today it works as a vital cultural mediator, as cross-linguistic and cross-cultural communication. In the present article we intend to discuss the changes in the translator’s work triggered by the so-called globalization.